Perbandingan Nilai Sosial dalam Novel Ivanna Van Dijk dengan Novel Ananta Prahadi Karya Risa Saraswati melalui Pendekatan Sosiologi Sastra - Agung Nugroho; Yasafiq Yasafiq (LP4MK STKIP PGRI Lubuklinggau, 2019)
The purpose of this study was to describe the comparison of Ivanna Van Dijk novel by Risa Saraswati with the novel Ananta Prahadi by Risa Saraswati through a sociology approach. This research method is a qualitative descriptive research method. The research data is data in the form of words, phrase phrases or sentence which show social values ​​in Ivanna Van Dijk novel by Risa Saraswati with the novel Ananta Prahadi by Risa Saraswati. Data analysis techniques by reducing data, presenting data, and drawing conclusions. The results showed that Ivanna Van Dijk novel by Risa Saraswati with the novel Ananta Prahadi by Risa Saraswati had similarities, namely dominant in the social value of human nature to others in social life, so that the story was easy to understand. The difference is that the value of Ivana Van Dijk social novel by Risa Saraswati tends to be more about the nature of human relations which considers life to be bad while in Ananta Prahadi novels tends to social values ​​in the form of human relations with each other, it means that dealing with others is something that is not good or even only will have a bad impact and can hinder everything he wants to do, he is amazed that it can solve all problems by itself without requiring help from anyone. Furthermore, Ananta Prahadi novel does not lead to horror stories, unlike the Ivana Van Dijk novel whose stories contain horror stories.